2019
DOI: 10.1016/j.jmaa.2019.123382
|View full text |Cite
|
Sign up to set email alerts
|

Cake-cutting with different entitlements: How many cuts are needed?

Abstract: A cake has to be divided fairly among n agents. When all agents have equal entitlements, it is known that such a division can be implemented with n − 1 cuts. When agents may have different entitlements, the paper shows that at least 2n − 2 cuts may be necessary, and O(n log n) cuts are always sufficient.JEL classification: D63

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The negative result (b) follows immediately from an identical negative result for individual agents (Segal-Halevi 2019), by considering k one-member families.…”
Section: Average Fairnessmentioning
confidence: 86%
“…The negative result (b) follows immediately from an identical negative result for individual agents (Segal-Halevi 2019), by considering k one-member families.…”
Section: Average Fairnessmentioning
confidence: 86%
“…While we trivially have f(n)n1 for n2, it is not hard to do better. The following construction from [7] shows that f(n)2n2 for all n2. Let μ1 be the uniform measure on [0,1] and for 1in1, let μi+1 be the uniform measure supported on the (tiny) interval [i/nε,i/n+ε], where ε=1/(100n)10.…”
Section: Resultsmentioning
confidence: 99%
“…What if we ask for an efficient disproportionate division with a bounded number of cuts? A beautiful topological result of Stromquist and Woodall [11] furnishes an answer; a folklore argument utilising this result shows that a disproportionate division for n agents with arbitrary demands may always be found with O(n2) cuts, and a more efficient rendition of this argument, recently discovered by Segal‐Halevi [7], shows that in fact O(nlogn) cuts always suffice. Our main result improves on these decades‐old topological arguments as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature on cake-cutting is about the search for a fair division into pieces that get allocated to the agents (such that, for example, no agent values someone else's pieces more than his own), as opposed to consensus division, as considered here. In the context of fair division, there is an "arbitrary proportions" analogue to the problem studied in this paper: Segal-Halevi [Seg19] and Crew et al [CNS20] have studied an analogous generalisation of fair division in which each agent has a (non-negative fractional) claim on the cake, all claims summing to 1. In common with consensus division, it is found that in the more general case of unequal proportions, more cuts may be required than in the special case of equal proportions.…”
Section: Background Related Workmentioning
confidence: 99%